Who is Buried in Chaucer''s Tomb? : Studies in the Reception of Chaucer''s Book. - Dane, Joseph A. (Michigan State University Press, 1998)
Joseph A. Dane examines the history of the books we now know as ""Chaucer's""--A history that includes printers and publishers, editors, antiquarians, librarians, and book collectors. The Chaucer at issue here is not a medieval poet, securely bound within his fourteenth-century context, but rather the product of the often chaotic history of the physical books that have been produced and marketed in his name. This history involves a series of myths about Chaucer-a reformist Chaucer, a realist Chaucer, a political and critical Chaucer who seems oddly like us. It also involves more self.